Pelican Island, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2011)
This postcard shows Pelican Island, which is one of islands in the group known as the "Five Islands” which are actually six islands located west of Port of Spain in the Gulf of Paria. The others are Caledonia, Craig, Nelson, Lenagan, Rock Islands.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Paria, Gulf of (Venezuela and Trinidad and Tobago); Islands--Trinidad and Tobago; 1915; Vacation homes--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Bodies of water--Trinidad and Tobago; Five Islands, The